2005
DOI: 10.1097/01.ccm.0000178351.03327.9f
|View full text |Cite
|
Sign up to set email alerts
|

B-type natriuretic peptide: Issues for the intensivist and pulmonologist

Abstract: Intensivists and pulmonologists should understand that BNP and NT-proBNP levels might be raised to different degrees not only in heart failure but also in critical illness and various pulmonary diseases; in these situations, BNP and NT-proBNP may also serve as markers of severity and prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 150 publications
0
65
0
4
Order By: Relevance
“…19,20 More recently, it has been reported that the increase in these biomarkers may indicate the underlying subclinical predisposition to AF both in patients undergoing cardiac surgery 21 and in patients without a history of cardiac disease. 22 However, the capability of NT-proBNP to predict postoperative AF has never been evaluated prospectively; therefore, its clinical applicability remains unclear, as does its transferability to other clinical settings.…”
Section: Clinical Perspective P 1344mentioning
confidence: 99%
“…19,20 More recently, it has been reported that the increase in these biomarkers may indicate the underlying subclinical predisposition to AF both in patients undergoing cardiac surgery 21 and in patients without a history of cardiac disease. 22 However, the capability of NT-proBNP to predict postoperative AF has never been evaluated prospectively; therefore, its clinical applicability remains unclear, as does its transferability to other clinical settings.…”
Section: Clinical Perspective P 1344mentioning
confidence: 99%
“…However, the present data should be sufficient to draw conclusions that could potentially guide clinical practice. Since the plasma BNP level can also be affected by multiple disorders (including cardiac diseases, shock, pulmonary hypertension, acute pulmonary embolism, chronic obstructive pulmonary disease and renal failure), 24 caution should be taken when using BNP in the evaluation of patients with ALI/ARDS in combination with such conditions.…”
Section: Discussionmentioning
confidence: 99%
“…or proinflammatory cytokines (18,19), volume resuscitation (20), and sepsis-associated acute lung injury or acute respiratory distress syndrome (21). Clinical severity scores such as acute physiology and chronic health evaluation (APACHE) II as well as sequential organ failure assessment (SOFA) scores have been validated as poor-outcome stratifications in patients with sepsis, but are unwieldy and tend to be used more for audit and research than clinical decision making.…”
Section: Discussionmentioning
confidence: 99%